2013
DOI: 10.1186/1471-2156-14-47
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for backfat thickness in Canchim beef cattle using Random Forest approach

Abstract: BackgroundMeat quality involves many traits, such as marbling, tenderness, juiciness, and backfat thickness, all of which require attention from livestock producers. Backfat thickness improvement by means of traditional selection techniques in Canchim beef cattle has been challenging due to its low heritability, and it is measured late in an animal’s life. Therefore, the implementation of new methodologies for identification of single nucleotide polymorphisms (SNPs) linked to backfat thickness are an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 83 publications
0
27
1
2
Order By: Relevance
“…; Mokry et al . ). Random Forest has recently been used in a conservation context to identify SNPs associated with traits relevant to climate adaptation in conifers (Holliday et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Mokry et al . ). Random Forest has recently been used in a conservation context to identify SNPs associated with traits relevant to climate adaptation in conifers (Holliday et al .…”
Section: Introductionmentioning
confidence: 97%
“…Although chromosome 7 exhibited a larger number of significant SNPs (P < 0.001), chromosomes 1 and 2 contained regions of less dispersed significant SNPs (P < 0.001) (Figure 1 and Table 3). Using the BovineHD BeadChip to genotype 400 Canchim animals, Mokry et al (2013) also identified significant SNPs for BF on chromosome 1, in addition to chromosomes 3, 10, 13, and 19. QTLs for BF have been identified on chromosomes 2, 3, 7, and 14 of crossbred cattle (Brahman x Hereford) (Casas et al, 2003).…”
Section: Chromosomementioning
confidence: 99%
“…Using a chip with a higher density of markers (BovineSNP50 BeadChip), Nishimura et al (2012) identified SNPs associated with carcass weight on chromosomes 6, 8, and 14 of Japanese Black cattle. Mokry et al (2013) genotyped 400 Canchim cattle using the BovineHD BeadChip. The authors found an association between SNPs and BF, indicating regions with potential QTLs for this trait on chromosomes 1, 3, 13, and 19.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre eles, MOKRY et al (2013) utilizaram Random Forest para a identificação de marcadores SNP ligados à espessura de gordura de gados Canchim. LEWIS et al (2011) aplicaram Análise de Componentes Principais (PCA) para a identificação de SNP relevantes na rastreabilidade de bovinos.…”
unclassified
“…Outros trabalhos abordaram seleção de atributos em suínos (CORDEIRO et al, 2012) e humanos (WU et al, 2012), porém são raros os trabalhos envolvendo dados de ovinos. De forma geral, observou-se que os trabalhos relacionados selecionaram um número menor que 100 marcadores SNP em seus resultados finais (MOKRY et al, 2013;SASAZAKI et al, 2011;SUEKAWA et al, 2010), número a que este trabalho buscou referenciar-se como limite para a seleção dos SNPs mais informativos. Além disso, considerou-se o possível desenvolvimento de um microarranjo de baixa densidade, que aloca múltiplos de 48 marcadores SNP em sua superfície (ROORKIWAL et al, 2013).…”
unclassified